Self-directed learning in health professions: A mixed-methods systematic review of the literature. - Joana Berger-Estilita; Linda Krista; Artemisa Gogollari; Felix Schmitz; Achim Elfering; Sissel Guttormsen (PLoS ONE)
Purpose This study investigated the application and effectiveness of various self-directed learning (SDL) models in healthcare organizations. This study aims to identify the prevalent SDL models and factors influencing SDL adoption in healthcare settings. Methods A systematic review was conducted, encompassing a comprehensive search across multiple academic databases (MEDLINE, Embase, PsycINFO, ERIC, and the Cochrane Library). The final search was conducted on April 16, 2024. The inclusion criteria were studies involving health and allied health professionals in clinical settings that explored SDL in any context or form of activity, emphasizing the description and/or use of an SDL model or SDL-related concept. Both qualitative and quantitative studies were included. We also explored the factors facilitating or hindering SDL and specific SDL-related outcomes, accommodating various study designs. Results The final review synthesized findings from 34 articles involving over 5,700 healthcare professionals (including nurses, pharmacists, and physicians). The findings reveal that supportive organizational cultures significantly enhance SDL practices, whereas restrictive policies hinder their effectiveness. Various SDL models were identified and examined, showing that integrative frameworks combining individual motivation with structured organizational support yielded the best outcomes in fostering lifelong learning and adaptability among healthcare professionals. These findings emphasize the significance of individual motivation, learning environment, technological resources, social interactions, and SDL readiness among healthcare professionals. Conclusion Our findings demonstrate that SDL is crucial for the continuous professional development of healthcare providers and should be strategically supported by healthcare organizations. This study contributes to a better understanding of the interplay between SDL, workplace dynamics, and digital technology in healthcare practices. Identifying prevalent SDL models and factors influencing their adoption offers valuable insights for healthcare professionals on effective implementation strategies that address both its barriers and facilitators. Systematic review registration reviewregistry1309, February 28, 2022 (www.researchregistry.com).